Effect of a probiotic hacterium, Lactobacillus plantarum on disease resistance of Penaeus indicus larvae - Uma, A; Abraham, Jawahar; Sundararaj, V (Indian Journal of Fisheries, 2011)
The effect of a probiotic bacteirum, Lactobacillus plantarum on the disease resistance of penaeid shrimp, Panaeus indicus (H. Milne Edwards) larvae against the antibiotic resistant luminous Vibrio harveyi was investigated. Vibrio harveyi, isolated from the diseased shrimp larvae, induced mortality in experimentally infected mysis larvae within 12 hours of post-challenge and caused 83% mortality in 72 hours at 1.28 x 10’* cells/ml level. Addition of the probiont in shrimp larval rearing medium from lO’’ to 10^ cells/ml improved the growth and survival of P. indicus larvae, with 10^ cells/ml being the most effective level. Bioencapsulation of the probiont (>10’’ cells/g Artemia sp.) greatly improved the dietary value of Artemia sp. nauplii and increased the disease resistance of shrimp larvae. A significant weight gain (> 70 %) was observed in probiont (lO"* cells/g Artemia sp.) fed larvae compared to the control group. Larvae grown in the presence of the probiont resisted V. harveyi infection when challenged.